Live Monitoring: Using Adaptive Instrumentation and Analysis to Debug and Maintain Web Applications - Kiciman, Emre; Wang, Helen (The 11th Workshop on Hot Topics in Operating Systems (HotOS XI), 2007)
AJAX-based web applications are enabling the next generation of rich, client-side web applications, but today’s web application developers do not have the end-to-end visibility required to effectively build and maintain a reliable system. We argue that a new capability of the web application environment—the ability for a system to automatically create and serve different versions of an application to each user—can be exploited for adaptive, cross-user monitoring of the behavior of web applications on end-user desktops. In this paper, we propose a live monitoring framework for building a new class of development and maintenance techniques that use a continuous loop of automatic, adaptive application rewriting, observation and analysis. We outline two such adaptive techniques for localizing data corruption bugs and automatically placing function result caching. The live monitoring framework requires only minor changes to web application servers, no changes to application code and no modifications to existing browsers.